2002
DOI: 10.1902/jop.2002.73.11.1308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 Laser Treatment on Fibroblast Attachment to Root Surfaces. A Scanning Electron Microscopy Analysis

Abstract: CO2 laser treatment in defocused, pulsed mode with a low power of 2W combined with mechanical instrumentation constitutes a useful tool to condition the root surface and increase fibroblast attachment to root surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 18 publications
1
51
0
Order By: Relevance
“…The application of diode laser did not increase the numbers of attached cells after scaling and root planing [19]. CO 2 laser in combination with ultrasonic scaling was compared with hand scaling and root planing, and both promoted cell attachment being more pronounced for the additional application of laser [20]. In contrast, more PDL fibroblasts attached to surfaces pretreated with Er:YAG laser or ultrasonic scalers than with SRP [21].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The application of diode laser did not increase the numbers of attached cells after scaling and root planing [19]. CO 2 laser in combination with ultrasonic scaling was compared with hand scaling and root planing, and both promoted cell attachment being more pronounced for the additional application of laser [20]. In contrast, more PDL fibroblasts attached to surfaces pretreated with Er:YAG laser or ultrasonic scalers than with SRP [21].…”
Section: Discussionmentioning
confidence: 91%
“…All specimens were first covered with serum to simulate the in vivo situation in periodontal pockets; serum proteins are an essential component of gingival crevicular fluid [23]. Nearly no rounded fibroblasts were observed like in other studies [20,21], suggesting that neither the specimens nor the treatment damaged the cells. The number of attached PDL fibroblasts was doubled after the additional instrumentation with the diamond-coated curette.…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical studies, it has been demonstrated that lasers are an effective tool in the field of root conditioning to improve the outcome of regenerative periodontal therapies by favoring the attachment of the regenerated periodontal structures. [32][33][34][35][36][37][38][39][40][41][42][43] The Nd:YAG laser has been reported to remove the smear layer, uncovering dentinal tubules and exposing collagen fibers on root surfaces. 37,38 The Nd:YAG laser, with noncontact delivery mode and short irradiation time, has caused no damage to or alteration of root surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition to chemical conditioning, the applicability of different laser systems such as CO 2 , Nd:YAG, diode and Er:YAG laser in the removal of the smear layer have been demonstrated. [32][33][34][35][36][37][38][39][40][41][42][43] However, until now, no published data have been available concerning the clinical outcomes following root surface biomodification with Nd:YAG laser for the treatment of gingival recession. Therefore, the aim of the present study was to evaluate and compare the outcome of gingival recession therapy using the SCTG with or without Nd:YAG laser application for root surface biomodification.…”
mentioning
confidence: 99%
“…Lasers have been studied for their effect on root surface [76][77][78][79][80][81][82] as well as for their effects on the behaviour on periodontal ligament cells [83][84][85]. Although, laser therapy has been widely studied in periodontics for pocket debridement, wound healing and in various surgical approaches but there is insufficient data available regarding its efficacy in root surface biomodification when compared with other traditionally used root surface conditioners.…”
Section: Hyaluronic Acid (Ha) Lasersmentioning
confidence: 99%